Fraud Diamond Perspective in Detecting and Understanding Financial Reporting Irregularities in Publicly Listed Companies - Rina Deviani; Ferdiansyah Ferdiansyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the impact of pressure, opportunity, rationalization, and capability as defined by the Fraud Diamond Theory Wolfe & Hermanson, 2004 on fraudulent financial reporting indicators in energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. A quantitative approach employing multiple linear regression was adopted. Secondary data were extracted from annual financial statements published on the IDX website. Pressure was proxied by the debt-to-assets ratio, opportunity by a corporate governance index, rationalization by audit opinion, and capability by changes in the board of directors. Fraudulent reporting was identified using the Beneish M-Score model. The sample comprised 52 companies selected via purposive sampling based on predefined criteria. Opportunity and rationalization exhibited a statistically significant positive relationship with financial statement fraud. In contrast, pressure and capability showed no significant effect. This study validates the Fraud Diamond Theory in Indonesia’s energy sector, highlighting corporate governance and auditor oversight as critical fraud predictors. It offers empirical evidence for regulators to prioritize governance reforms and audit transparency over conventional leverage-based risk assessments.